2015
DOI: 10.1002/2014wr016108
|View full text |Cite
|
Sign up to set email alerts
|

Ecohydrology in semiarid urban ecosystems: Modeling the relationship between connected impervious area and ecosystem productivity

Abstract: In water-stressed, semiarid urban environments, connections between impervious surfaces and drainage networks may strongly impact the water use and ecosystem productivity of neighboring vegetated areas. We use an ecohydrologic model, the Regional Hydro-Ecological Simulation System (RHESSys), to quantify the sensitivity of vegetation water use and net primary productivity (NPP) to fine-scale impervious surface connectivity. We develop a set of very fine-scale (2 m 2 ) scenarios that vary both the percentage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 27 publications
4
40
0
Order By: Relevance
“…In particular, county‐level estimates of LU change available in Wear () were further refined to a 30‐m spatial scale, consistent with the resolution of the NLCD. The ecohydrological model (RHESSys) used in the study is often used at a 30‐m or finer scales (Mittman, Band, Hwang, & Smith, ; Mohammed & Tarboton, ; Shields & Tague, ). Due to a combination of available data on land cover, digital elevation models and processing time (smaller spatial scales are more computationally intensive) resolutions of <30 m are generally used in smaller watersheds.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, county‐level estimates of LU change available in Wear () were further refined to a 30‐m spatial scale, consistent with the resolution of the NLCD. The ecohydrological model (RHESSys) used in the study is often used at a 30‐m or finer scales (Mittman, Band, Hwang, & Smith, ; Mohammed & Tarboton, ; Shields & Tague, ). Due to a combination of available data on land cover, digital elevation models and processing time (smaller spatial scales are more computationally intensive) resolutions of <30 m are generally used in smaller watersheds.…”
Section: Methodsmentioning
confidence: 99%
“…Since UI is inherently bounded by the watershed's TI, the ratio of the two (UI/TI) is another metric that characterizes the fraction of TI that is directly connected to the stream. This metric is analogous to drainage connection and effective impervious area fraction used in other studies (Shields & Tague, 2014;Walsh et al, 2005;Walsh & Kunapo, 2009).…”
Section: Site Descriptionmentioning
confidence: 99%
“…This metric captures connectivity and extent of impervious surfaces. Modeling studies have shown that EI predicts runoff volumes and storm event peak discharges well (Dewals et al, ; Guo, ; Lee & Heaney, ; Palla & Gnecco, ; Schoener, ; Shields & Tague, ). However, there is currently a lack of empirical studies examining the watershed‐scale effects of connectivity to SCMs on water quality, and only a few modeling studies exist (Jefferson et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple lines of evidence indicated that urban ecosystem NPP is sensitive to environmental changes at various spatiotemporal scales. Previous studies have investigated inter-annual variability of NPP in response to climate change [10][11][12][13], the contributions of urbanization and climate change to NPP variations [14][15][16][17], and the effect of urban land transformation on NPP [18]. Most research has been focused on the effect of land use/land cover change and historical climate change; however, the dynamic of NPP in response to future climate/CO 2 change effects are still unclear.…”
Section: Introductionmentioning
confidence: 99%